AI at the Helm in Redefining Financial Governance: The Role of AI in Shaping Financial Leadership and Strategy (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines how artificial intelligence (AI) is reshaping financial leadership and governance. The research problem addressed is the limited understanding of AI’s direct influence on governance effectiveness. The primary objective was to assess the role of AI in leadership transformation and strategic financial planning. Given the modest sample size and the quantitative design, this study was viewed as exploratory, offering preliminary evidence on the role of AI in financial governance rather than conclusive generalizations. Positivist approach, data were collected from 50 professionals in finance, accounting, and corporate governance through a structured questionnaire that covered six domains. Reliability tests confirmed strong internal consistency, and regression analysis revealed that AI-driven leadership transformation and AI in strategic planning significantly enhance financial leadership effectiveness. In contrast, adoption, compliance, and organizational context showed no direct impact, though they may serve as enabling conditions. The findings recommend prioritizing leadership-oriented AI strategies to strengthen governance outcomes. The study concludes that harnessing AI to revolutionize leadership and embed it into strategic financial planning is essential for elevating governance. True financial leadership requires rethinking roles and strategically using AI to drive smarter decisions, with leaders’ vision ultimately propelling real progress in financial governance.